A Comparative Analysis of Traditional RDBMS with MapReduce and Hive for E-Governance system (International Journal of Engineering and Computer Science, 2017)
India is moving towards digitization. Most of the state and central governments are digitizing the departments due to which the use of E-governance applications has increased. As a result data is getting added in large size daily. Hadoop and MapReduce are used to handle these large volumes of variable size data. Processing and sharing of such a large data by traditional methods is difficult by the use of traditional methods. What is important is the speed at which one can process that data and extract the actionable business intelligence information. In this paper we present the comparison of traditional RDBMS with MapReduce technique and use of HiveQL to implement MapReduce on large databases. The paper also focuses on use of Sqoop connector to connect SQL and Hadoop that illustrates how big data can result in the transformation of the government by increased efficiency and effectiveness in the E-governance service.